Inhibition of nitric oxide synthesis improves left ventricular contractility in neonatal pigs late after cardiopulmonary bypass. Issue 6 (1st December 1999) - Chaturvedi, R R; Hjortdal, V E; Stenbog, E V; Ravn, H B; White, P; Christensen, T D; Thomsen, A B; Pedersen, J; Sorensen, K E; Redington, A N
Abstract : BACKGROUND: Following neonatal open heart surgery a nadir occurs in left ventricular function six to 12 hours after cardiopulmonary bypass. Although initiated by intraoperative events, little is known about the mechanisms involved. OBJECTIVE: To evaluate the involvement of nitric oxide in this late phase dysfunction in piglets. DESIGN: Piglets aged 2 to 3 weeks (4–5 kg) underwent cardiopulmonary bypass (1 h) and cardioplegic arrest (0.5 h) and then remained ventilated with inotropic support. Twelve hours after bypass, while receiving dobutamine (5 μg/kg/min), the left ventricular response to non-selective nitric oxide synthase inhibition (l-N G -monomethylarginine (l-NMMA)) was evaluated using load dependent and load independent indices (Ees, the slope of the end systolic pressure–volume relation; Mw, the slope of the stroke work–end diastolic volume relation; [dP/dtmax ]edv, the slope of the dP/dtmax –end diastolic volume relation), derived from left ventricular pressure–volume loops generated by conductance and microtip pressure catheters. RESULTS: 10 pigs received 7.5 mg l-NMMA intravenously and six of these received two additional doses (37.5 mg and 75 mg). Ees (mean (SD)) increased with all three doses, from 54.9 (40.1) mm Hg/ml (control) to 86.3 (69.5) at 7.5 mg, 117.9 (65.1) at 37.5 mg, and 119 (80.4) at 75 mg (p < 0.05). At the two highest doses, [dP/dtmax ]edv increased from 260.8 (209.3) (control) to 470.5 (22.8) at 37.5 mg and 474.1 (296.6) at 75 mg (p < 0.05); and end diastolic pressure decreased from 16.5 (5.6) mm Hg (control) to 11.3 (5.0) at 37.5 mg and 11.4 (4.9) at 75 mg (p < 0.05). CONCLUSIONS: In neonatal pigs 12 hours after cardiopulmonary bypass with ischaemic arrest, low dose l-NMMA improved left ventricular function, implying that there is a net deleterious cardiac action of nitric oxide at this time.